2017
DOI: 10.1186/s12967-017-1156-1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and smooth muscle cells derived from human cardiac explants demonstrate angiogenic potential and suitable for design of cell-containing vascular grafts

Abstract: BackgroundEndothelial and smooth muscle cells are considered promising resources for regenerative medicine and cell replacement therapy. It has been shown that both types of cells are heterogeneous depending on the type of vessels and organs in which they are located. Therefore, isolation of endothelial and smooth muscle cells from tissues relevant to the area of research is necessary for the adequate study of specific pathologies. However, sources of specialized human endothelial and smooth muscle cells are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…For experimental mouse or human intestinal and colorectal tissues, IHC and IF staining was performed as previously described [20, 21]. The study methodologies were approved by the local ethics committee, and the following primary antibodies were used: AIBP (Abcam, ab81907, 1:300 dilution), APOA-I (Bioss, bs-0849R, 1:300 dilution) and CD31 antibody (Abcam, ab28364, 1:300 dilution).…”
Section: Methodsmentioning
confidence: 99%
“…For experimental mouse or human intestinal and colorectal tissues, IHC and IF staining was performed as previously described [20, 21]. The study methodologies were approved by the local ethics committee, and the following primary antibodies were used: AIBP (Abcam, ab81907, 1:300 dilution), APOA-I (Bioss, bs-0849R, 1:300 dilution) and CD31 antibody (Abcam, ab28364, 1:300 dilution).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac ECs and SMCs not only promote the vascularization and survival of transplanted hCMPs but are also key mediators of the signaling mechanisms that regulate CM activity (23,48,49). Cardiac fibroblasts can further improve CM survival by remodeling the extracellular matrix (ECM) and releasing cytoprotective paracrine factors (6,9,(50)(51)(52).…”
Section: Cardiac Vascular Cells and Fibroblastsmentioning
confidence: 99%
“…In our previous study, we found that surgical discarded cardiac tissue as a right atrial appendage and right ventricular myocardium is an available source for functional endothelial and smooth muscle cells potentially suitable for vascular tissue engineering ( Zakharova et al, 2017 ). We derived endothelial and smooth muscle cell cultures from human cardiac post-operative explants.…”
Section: Introductionmentioning
confidence: 99%